High-tap-density silver powder and preparation method and application thereof

By reacting in alcohol amine and organic amine solutions to generate silver powder with different particle sizes, and processing by hydrothermal and dispersant, the problems of silver powder dispersion and low tap density are solved, and the printing performance of silver paste and solar cells are improved. efficiency.

CN119319257AActive Publication Date: 2025-01-17HA SHEN TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411461862.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-17
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

In the prior art, the poor dispersion and low tap density of silver powder lead to poor printing performance and affect the photoelectric conversion efficiency of solar cells.

Method used

By dispersing the silver salt in the alcohol amine solution and reacting with the organic amine solution, silver powder with different particle sizes is generated, the filling structure is tight, the tap density is improved, and the particle size and dispersion are controlled through hydrothermal reaction, combining dispersants and Cleaning and recycling process to improve the sintering performance of silver powder.

Benefits of technology

The high tap density and good dispersion of silver powder are achieved, the fluidity and sintering performance of silver paste are improved, and the photoelectric conversion efficiency of solar cells is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005092074990000011
    Figure HDA0005092074990000011
  • Figure HDA0005092074990000012
    Figure HDA0005092074990000012
  • Figure HDA0005092074990000021
    Figure HDA0005092074990000021
Patent Text Reader

Abstract

The invention discloses silver powder with high tap density and a preparation method and application thereof, and the preparation method of the silver powder comprises the following steps: dispersing silver salt in an alcohol amine solution, and then reacting with an organic amine solution to prepare silver particles. According to the preparation method of the silver particles, spherical powder with different particle sizes can be prepared, silver paste prepared from the spherical silver powder generally has better fluidity, the silver particles with large particle sizes and the silver particles with small particle sizes are filled with one another, the sufficient contact area between the silver powder is ensured, and the requirement of the front silver paste for the performance of the silver powder can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to a silver powder with high tap density and a preparation method and application thereof. Background Art

[0002] Silver powder has excellent electrical conductivity, thermal conductivity and corrosion resistance, and is widely used in the electronics industry, aerospace, and materials fields. In recent years, the application of silver powder in the photovoltaic field has become increasingly common. Silver powder is used as a conductive material in heterojunction batteries. The application of high-temperature / low-temperature silver paste technology has made the application of silver powder in this field more extensive. A series of parameters such as the morphology, particle size, and tap density of silver powder are related to the printing performance of the conductive paste, thereby determining the photoelectric conversion efficiency of solar cells. However, silver powder currently generally has problems with poor dispersibility and low tap density, resulting in poor printability after being made into silver paste; therefore, the preparation of micron silver powder with good dispersibility and high tap density is one of the key factors in improving the photoelectric conversion rate of solar cells.

[0003] At present, the only method for preparing silver powder that can be mass-produced in China is the liquid phase reduction method, which uses a peristaltic pump to add reducing liquid and dispersing liquid to the silver salt solution in a timed and quantitative manner to prepare silver powder. The dispersion of the silver powder particles produced by this method is difficult to control, and the tap density is generally low. Summary of the invention

[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the object of the present invention is to provide a silver powder with high tap density and a preparation method and application thereof.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The first aspect of the present invention provides a method for preparing silver particles, comprising the following steps: dispersing a silver salt in an alcohol amine solution, and then reacting with an organic amine solution to obtain the silver particles.

[0007] In the present invention, the reduction rates of the silver salt by the alcohol amine solution and the organic amine solution are different, thereby producing silver powders of different particle sizes, and the small-particle silver powder is filled into the gaps between the larger-particle silver powder, so that the gaps between the silver powder particles become smaller, resulting in a more compact overall structure of the silver powder, thereby increasing the tap density of the silver powder. At the same time, compared with the single large-particle or small-particle silver powder, the silver powder of different particle sizes can accelerate the sintering process, and the larger-particle silver powder can still maintain a good shape at a higher temperature, thereby improving the structural stability of the sintered body and improving the overall sintering performance of the silver powder. On the other hand, the alcohol amine solution is used as an auxiliary reducing agent and the organic amine is used as the main reducing agent. The combination of the two can increase the rate of the reduction reaction, thereby accelerating the generation rate of the silver powder; further, the alcohol amine solution itself is weakly alkaline, and the first addition of the alcohol amine solution can provide an alkaline environment for the subsequent addition of the organic amine solution and its reaction with the silver salt, which is conducive to the reduction reaction of the organic amine and the silver salt.

[0008] In some embodiments of the present invention, the molar ratio of the alcoholamine compound in the alcoholamine solution to the silver ions in the silver salt is 0.05 to 5:1, such as 0.1:1, 0.5:1.0, 1:1, 1.5:1, 2.0:1, 2.5:1, 3.0:1, 3.5:1, 4.0:1, 4.5:1, etc.; if the concentration of silver ions is too high, it may be difficult to effectively disperse; the addition of alcoholamine can increase the rate of reduction reaction between the organic amine solution and the silver salt, accelerate the generation rate of silver powder, improve the purity of the silver powder, and reduce the occurrence of side reactions.

[0009] In some embodiments of the present invention, the molar concentration of the silver salt is controlled so that its molar concentration before adding the organic amine solution is 0.008-5.0 mol / L, such as 0.1 mol / L, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4.0 mol / L, 4.5 mol / L.

[0010] In some embodiments of the present invention, the molar ratio of the organic amine compound in the organic amine solution to the silver ion in the silver salt is 0.005-0.15:1, such as 0.008:1, 0.01:1, 0.03:1, 0.05:1, 0.08:1, 0.1:1, 0.12:1, etc.

[0011] In some embodiments of the present invention, the silver salt includes at least one of silver sulfate, silver nitrate, silver oxide, silver acetate, silver oxalate, silver phosphate, silver hexafluorophosphate, silver tetrafluoroborate, silver hexafluoroarsenate, silver chromate, silver chloride, silver bromide, silver iodide, silver carbonate, silver bicarbonate, silver benzoate, silver tartrate, silver laurate, silver perchlorate, and silver perbromide.

[0012] In some embodiments of the present invention, the alcoholamine solution includes a solution of at least one of diethanolamine, methyldiethanolamine, ethanolamine, dimethylethanolamine, diglycolamine, isopropanolamine, triisopropanolamine, oleic acid diethanolamide, stearic acid diethanolamide, lauric acid diethanolamide and octadecyl diethanolamine.

[0013] In some embodiments of the present invention, the organic amine solution includes a solution of at least one of triethylamine, N,N-diisopropylethylamine, tri-n-propylamine, triisopropylamine, tri-n-butylamine, cyclohexylamine, N,N-dimethyloctylamine, N,N-dimethyldecylamine, tri(3,6-dioxaheptyl)amine, and octylamine.

[0014] In some embodiments of the present invention, the pH of the organic amine solution is controlled to be 10-13, such as 10.5, 11, 11.5, 12, 12.5, etc.; the pH value of the organic amine solution can be controlled within this range by using a pH adjusting agent such as at least one of monoethanolamine, triethanolamine, and sodium hydroxide, so as to facilitate the reduction reaction, and the particle size of the silver powder precipitated by reduction decreases with the increase of the reaction pH.

[0015] In some embodiments of the present invention, the reaction is a hydrothermal reaction; the reaction temperature of the reaction is 75-235°C, such as 75-170°C, 90-210°C, 90-155°C, 100-200°C, 120-180°C, etc.; the reaction time of the reaction is 0.5-12h, such as 1-10h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, etc.; the hydrothermal reaction can be temperature controlled by methods known in the art, and a common method is to place the hydrothermal reaction kettle in an oven for temperature control; to improve the uniformity of the reaction, the hydrothermal reaction can be carried out under stirring, and the stirring rate can be controlled at 200-500rpm.

[0016] In the method for manufacturing silver powder of the present invention, the yield, purity and particle size of the silver powder can be controlled by controlling the feed ratio of the reactants such as the alcohol amine solution and the organic amine solution in the hydrothermal reaction, or by controlling the temperature and time of the hydrothermal reaction, thereby regulating the tap density of the silver powder.

[0017] In the method for manufacturing silver powder of the present invention, the alcohol amine solution and the organic amine solution are used in combination, which can accelerate the reduction rate of the organic amine to the silver salt, but will not make the reaction rate too fast, so there is no need to strictly control the pH or temperature of the mixed solution or the base solution of the alcohol amine solution and the silver salt; there is no need to control the temperature of the organic amine solution; after the organic amine solution is added, the system does not immediately undergo a hydrothermal reaction or the reaction rate is too fast, resulting in an uncontrolled reaction process and difficulty in effectively controlling the particle size of the product silver powder in the initial stage. After the organic amine solution is added, an additional stirring procedure can be performed before the hydrothermal reaction to improve the reaction uniformity, thereby easily controlling the particle size of the product silver powder.

[0018] In the method for manufacturing silver powder of the present invention, in order to improve the uniformity of the silver salt reaction and the dispersibility of the silver powder precipitated by reduction, the silver salt dispersion and the silver powder are treated with a dispersant, specifically, the silver salt is dispersed in an alcohol amine solution, and after adding the dispersant, it is reacted with an organic amine solution. The mass ratio of the dispersant to the silver atoms in the silver salt is (0.05-8):1. As the dispersant, a hydrophobic dispersant is preferably used, and at least one of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, sodium citrate, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, gelatin, methylcellulose, citric acid, Tween 60, propionic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, acrylic acid, oleic acid, linoleic acid, arachidonic acid, and ricinoleic acid can be used. By using the above-mentioned dispersant, the adsorption of the dispersant to silver and the dispersibility between silver particles can be taken into account to prevent the agglomeration of silver powder particles.

[0019] In the method for manufacturing silver powder of the present invention, after the hydrothermal reaction is completed to obtain a solid-liquid mixture, the solid-liquid mixture is washed and recovered. In the washing and recovery process, the slurry is dehydrated and the filter cake of the silver powder is washed. The washing in the washing and recovery process can be carried out, for example, using pure water. The dehydration in the washing and recovery process can be carried out, for example, by decantation or filter pressing. The end point of washing can be determined using the conductivity of the washing water. Specifically, the washing can be determined to be finished when the conductivity of the washing water is below a specified value, such as when its conductivity reaches 0.5 mS / m or less.

[0020] After the washing and recovery process is completed, a drying process is performed to dry the filter cake of the recovered silver powder. The drying process can use a vacuum drying or airflow dryer. In the drying process, a high-pressure air flow can be blown to the filter cake and the silver powder in the drying process, or the filter cake and the silver powder in the drying process can be put into a stirrer with a stirring rotor or a grinder with a grinding rotor for stirring, thereby giving a dispersing force to the filter cake and the silver powder in the drying process, and performing an operation to promote dispersion and drying.

[0021] In addition, in the drying process, the temperature of the silver powder may be set to 70° C. or less. If the temperature of the silver powder exceeds 70° C., the silver fine particles in the silver powder may be sintered.

[0022] At the same time as the drying process or after the drying process, a crushing, pulverizing or classification operation for adjusting the particle size distribution of the silver powder can be performed. The pulverizing operation can be performed using an air flow type or a mechanical pulverizer. The classification operation can be performed by using a classification rotor, a cyclonic wind classification, or by inertial force classification or a sieving operation.

[0023] The second aspect of the present invention provides silver powder obtained by the method for preparing silver particles.

[0024] In some embodiments of the present invention, the average particle size of the silver powder is 1.0-3.1 μm, such as 1.1-2.99 μm, 1.1-2.5 μm, 1.1-2.2 μm, etc.

[0025] In some embodiments of the present invention, the silver powder has a volume-based particle size distribution measured by a laser diffraction scattering particle size distribution measuring device, and the cumulative 50% particle size (D50) is 3.0 μm or less, such as 2.5 μm or less, 2.0 μm or less, 1.8 μm or less, or 1.7 μm or less; the cumulative 100% particle size (D100) is 20 μm or less, such as 18 μm or less, 15 μm or less, 12 μm or less, 10 μm or less, or 9 μm or less.

[0026] The volume-based particle size distribution of the silver powder adopts the particle size distribution measured by a laser diffraction scattering particle size distribution measuring device. In this embodiment, the following description is given of the case where the PSA particle size distribution measuring device PSA1090 (hereinafter simply recorded as a particle size distribution measuring device) manufactured by Anton Paar is used as the laser diffraction scattering particle size distribution measuring device. The particle size distribution of the silver powder can be dispersed in a prescribed dispersion medium, that is, the value measured in a wet manner. In this embodiment, 0.1 g of silver powder is added to 40 mL of isopropanol as a dispersion medium, and an ultrasonic homogenizer (manufactured by Nippon Seiki Co., Ltd., US-150T; 19.5 kHz, tip diameter 18 mm) is used to disperse for 2 minutes to prepare a dispersion liquid, and then the dispersion liquid is provided to a particle size distribution measuring device to measure the particle size distribution of the silver powder.

[0027] In this specification, regarding particle size distribution, the cumulative 50% particle diameter refers to the so-called median particle diameter. The cumulative 50% particle diameter refers to the diameter at which the volume-based accumulation of the amount of particles from the smaller particle diameter side in the particle size distribution reaches 50%. Similarly, the cumulative 100% particle diameter is the diameter at which the volume-based accumulation of the amount of particles from the smaller particle diameter side in the particle size distribution becomes 100%. Hereinafter, the cumulative 50% particle diameter and the cumulative 100% particle diameter on a volume basis are sometimes recorded as D50 and D100, respectively.

[0028] In some embodiments of the present invention, in the volume-based particle size distribution of silver powder, the ratio of the difference between the cumulative 90% particle size and the cumulative 10% particle size to the cumulative 50% particle size (Span, particle size distribution width) can be 2.20 or less, such as less than 2.10, less than 2.08, less than 2.01, or less than 2.00. The smaller the Span and the smaller the difference, the narrower the particle size distribution of the silver powder, the better its dispersibility, and the higher the overall tap density of the formed silver powder.

[0029] In some embodiments of the present invention, the tap density of the silver powder is 5.80 g / cm3 Above, such as 5.85g / cm 3 Above, 6.00g / cm 3 Above, 6.30g / cm 3 Above, 6.50g / cm 3 Above, 6.60g / cm 3 Above, 6.60~7.10g / cm 3 , 6.60~7.0g / cm 3 The tap density of silver powder is the apparent density of the silver powder in the container after a predetermined amount of silver powder is weighed and put into a container of a predetermined capacity, and the container is dropped at a predetermined height for a predetermined number of times (hereinafter referred to as after tapping), and is calculated by dividing the weight of the silver powder in the container by the apparent capacity of the silver powder in the container.

[0030] In some embodiments of the present invention, the tap density of the silver powder is a value obtained as follows: using a tap density measuring device (produced by Shibayama Science Co., Ltd., volume specific gravity measuring device SS-DA-2), 50 g of silver powder is weighed, put into a container (50 mL test tube), tapped 3,000 times at a vibration frequency of 200 (i.e., 200 vibrations per minute), and the weight of the silver powder is divided by the apparent volume (cm) of the silver powder after tapping. 3 It should be noted that the unit of tap density is "g / cm 3 "express.

[0031] In some embodiments of the present invention, the silver powder is spherical silver powder, and spherical means that when the silver powder is observed under a scanning electron microscope (SEM), the particles are spherical or nearly spherical, and the sphericity of 100 particles is less than 1.5, wherein the sphericity refers to the ratio of the longest diameter to the shortest diameter when the particles are observed through SEM photos.

[0032] The third aspect of the present invention provides a conductive paste, comprising silver powder obtained by the preparation method of silver particles.

[0033] In some embodiments of the present invention, the preparation method of the conductive paste including the silver powder is carried out by dispersing the silver powder in a resin (binder) as a base material and a solvent.

[0034] In some embodiments of the present invention, the conductive paste includes the silver powder, a resin and a solvent.

[0035] In some embodiments of the present invention, an example of the resin used in preparing the conductive paste is epoxy resin, acrylic resin, polyester resin, polyimide resin, polyurethane resin, phenoxy resin, silicone resin, ethyl cellulose. Two or more resins may be used simultaneously.

[0036] In some embodiments of the present invention, an example of a solvent, ie, a dispersion medium, used to prepare the conductive paste is terpineol, butyl carbitol, butyl carbitol acetate, texanol-12. Two or more solvents may be used simultaneously.

[0037] In some embodiments of the present invention, the conductive paste may include components other than those mentioned above, such as glass frit, dispersant, surfactant, and viscosity modifier.

[0038] In some embodiments of the present invention, the conductive paste may be prepared, ie, dispersed and kneaded using ultrasonic dispersion, a disperser, a three-roll mill, a ball mill, a bead mill, a biaxial kneader, a rotation and revolution mixer, and the like.

[0039] In some embodiments of the present invention, the conductive paste using the silver powder of the present invention is suitable for forming a conductive film, that is, forming a conductive pattern and forming an electrode on a substrate. For example, it can be applied to various substrates such as silicon wafers for solar cells, films for touch panels, and glass for EL elements, or directly, or as required, on the film further provided with a transparent conductive film on the substrate, to form a conductive film by coating or printing. The conductive film obtained using the conductive paste of the present invention is suitable for use in, for example, collector electrodes of solar cell units, external electrodes of chip-type electronic components, RFID, electromagnetic wave shielding, vibrator bonding, membrane switches, electroluminescence, and other electrodes or electrical wiring applications.

[0040] In some embodiments of the present invention, the conductive paste is printed on the substrate by, for example, screen printing, offset printing, photolithography, etc., so that a conductive film of a desired shape can be formed.

[0041] The beneficial effects of the present invention are:

[0042] 1. The preparation method of silver particles of the present invention can produce spherical powders with different particle sizes. The silver paste prepared from spherical silver powder usually has better fluidity. Large-diameter and small-diameter silver particles fill each other to ensure sufficient contact area between the silver powders, which can meet the requirements of the positive silver paste for the performance of the silver powder.

[0043] 2. The preparation method of silver particles of the present invention can produce spherical powders with different particle sizes, which can be applied to high and low temperature sintering silver paste. When sintering, compared with single large particles or small particles, silver powders of different particle sizes can cooperate with each other during the sintering process. Small particles can accelerate the sintering process, while large particles can better maintain their shape at higher temperatures to improve structural stability, thereby improving the overall sintering performance. Therefore, compared with single large powder and single small powder, large and small mixed powders have sintering advantages and are suitable for solar cell manufacturing.

[0044] 3. The method for preparing silver particles of the present invention is an environmentally friendly method, can be carried out at relatively low temperature and pressure, and the by-products are usually easy to handle. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is a SEM image of the silver powder obtained in Example 1 of the present invention.

[0046] Figure 2 This is a SEM image of the silver powder obtained in Example 2 of the present invention.

[0047] Figure 3 This is a SEM image of the silver powder obtained in Example 3 of the present invention.

[0048] Figure 4 This is a SEM image of the silver powder obtained in Example 4 of the present invention.

[0049] Figure 5 This is a SEM image of the silver powder obtained in Example 5 of the present invention.

[0050] Figure 6 This is a SEM image of the silver powder obtained in Example 6 of the present invention.

[0051] Figure 7 This is a SEM image of the silver powder obtained in Comparative Example 1 of the present invention.

[0052] Figure 8 This is a SEM image of the silver powder obtained in Comparative Example 2 of the present invention.

[0053] Fig. 9 This is a SEM image of the silver powder obtained in Comparative Example 3 of the present invention.

[0054] Fig.10 This is a SEM image of the silver powder obtained in Comparative Example 4 of the present invention.

[0055] Fig.11 This is a SEM image of the silver powder obtained in Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0056] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0057] Example 1

[0058] This embodiment prepares a silver particle, and the specific process is as follows:

[0059] 1. Preparation before the experiment:

[0060] The alcohol amine solution uses dimethylethanolamine with an effective ingredient content of 98%, and the molar ratio of dimethylethanolamine to Ag is 2.25:1;

[0061] The dispersant is 98.5% oleic acid, and the mass of oleic acid is 6.14% of the mass of silver ions;

[0062] The organic amine solution uses octylamine with an effective ingredient content of 98%, and the molar ratio of octylamine to Ag is 0.0798:1;

[0063] Preparation of pH adjuster solution: 40% mass fraction of sodium hydroxide solution, the molar number of sodium hydroxide is approximately 0.58% of the molar number of silver ions

[0064] 2. Weigh 2 g of silver carbonate (silver ion molar amount is 0.0145 mol) and add it to the inner tank of the hydrothermal reactor. Then add 2.468 g of dimethylethanolamine and 0.1246 g of oleic acid. Place the inner tank on a magnetic stirrer and stir at 300 rpm until it is evenly stirred to obtain a base liquid.

[0065] 3. Add 0.0084 g of sodium hydroxide solution to 0.152 g of octylamine, adjust the pH value of octylamine to 12, and obtain a reducing agent solution;

[0066] 4. Pour the reducing agent solution into the inner tank of the hydrothermal reactor and mix it with the base liquid. Turn on the magnetic stirring at 300 rpm for 10 minutes, then place the inner tank in the hydrothermal reactor and place it in a 105°C oven for 3 hours.

[0067] 5. After the reaction, wait until the hydrothermal kettle cools down to room temperature (25°C), add deionized water and alcohol to the inner tank of the hydrothermal kettle after the reaction, wash and dry (drying temperature is 55°C, drying time is 2.5h) to obtain silver particles.

[0068] Example 2

[0069] This embodiment prepares a silver particle, and its preparation method is different from that of embodiment 1 in that the molar ratio of dimethylethanolamine to Ag is 4:1.

[0070] Example 3

[0071] This embodiment prepares a silver particle, and its preparation method is different from that of Example 1 in that the initial molar amount of silver ions is 4.5 mol, that is, the molar ratio of dimethylethanolamine to Ag is 0.00725:1, and the molar ratio of octylamine to Ag is 0.00025:1.

[0072] Example 4

[0073] This embodiment prepares a silver particle, and its preparation method is different from that of embodiment 1 in that the mass of oleic acid is 1.8% of the mass of silver ions.

[0074] Example 5

[0075] This embodiment prepares a silver particle, and its preparation method is different from that of embodiment 1 in that the molar ratio of octylamine to Ag is 0.12:1.

[0076] Example 6

[0077] This embodiment prepares a silver particle, and its preparation method is different from that of embodiment 1 in that the molar ratio of dimethylethanolamine to Ag is 8:1.

[0078] Example 7

[0079] This embodiment prepares a silver particle, and its preparation method is different from that of embodiment 1 in that: the organic amine solution uses cyclohexylamine with an effective ingredient content of 99%, and the molar ratio of cyclohexylamine to Ag is 0.0926:1.

[0080] Example 8

[0081] This embodiment prepares a silver particle, and its preparation method is different from that of embodiment 1 in that: the alcohol amine solution uses triisopropanolamine with an effective ingredient content of 95%, and the molar ratio of triisopropanolamine to Ag is 2:1.

[0082] Comparative Example 1

[0083] This comparative example prepared a silver powder, and the specific process was as follows:

[0084] 1. Preparation before the experiment is the same as in Example 1;

[0085] 2. Weigh 2 g of silver carbonate (silver ion molar amount is 0.0145 mol) and add it to the inner tank of the hydrothermal reactor. Add 2.468 g of dimethylethanolamine and 0.1246 g of oleic acid successively. Place the inner tank on a magnetic stirrer and stir at 300 rpm to obtain a base liquid. Stir at 300 rpm for 10 min, then place the inner tank in the hydrothermal reactor and place it in a 105 ° C oven for 3 h.

[0086] 3. After the reaction, wait until the hydrothermal kettle drops to room temperature (25°C), add deionized water and alcohol to the inner tank of the hydrothermal kettle after the reaction, wash and dry (drying temperature is 55°C, drying time is 2.5h) to obtain silver powder.

[0087] Comparative Example 2

[0088] This comparative example prepared a silver powder, and the specific process was as follows:

[0089] 1. Preparation before the experiment is the same as in Example 1;

[0090] 2. Weigh 2g of silver carbonate (silver ion molar amount is 0.0145mol) and add it to the inner tank of the hydrothermal reactor; add 0.0084g of sodium hydroxide solution to 0.152g of octylamine, adjust the pH value of octylamine to 12, and obtain a reducing agent solution; add the reducing agent solution and 0.1246g of oleic acid to the inner tank of the hydrothermal reactor; turn on the magnetic stirring at 300rpm and stir for 10min, then put the inner tank into the hydrothermal reactor and place it in a 105℃ oven for 3h;

[0091] 3. After the reaction, wait until the hydrothermal kettle drops to room temperature (25°C), add deionized water and alcohol to the inner tank of the hydrothermal kettle after the reaction, wash and dry (drying temperature is 55°C, drying time is 2.5h) to obtain silver powder.

[0092] Comparative Example 3

[0093] In this comparative example, a silver powder is prepared. The preparation method thereof is different from that of Example 1 in that hydrazine hydrate is used to replace the octylamine in Example 1, and the molar ratio of hydrazine hydrate to Ag is 0.0798:1.

[0094] Comparative Example 4

[0095] In this comparative example, a silver powder was prepared. The difference between the preparation method and that of Example 1 is that cyclohexylamine was used to replace the dimethylethanolamine in Example 1, and the molar ratio of cyclohexylamine to Ag was 2.25:1.

[0096] Comparative Example 5

[0097] In this comparative example, a silver powder was prepared. The difference between the preparation method and that of Example 1 is that diethanolamine was used to replace the octylamine in Example 1, and the molar ratio of diethanolamine to Ag was 0.0798:1.

[0098] Test Case

[0099] The obtained silver powder was characterized, and the results are shown in Table 1:

[0100] Table 1

[0101] Group Average particle size (μm) D50(μm) D100(μm) Span <![CDATA[Tap density (g / cm 3 )]]> Example 1 1.332 1.12 5.3 1.84 6.95 Example 2 1.13 0.9962 4 1.852 6.92 Example 3 1.2947 1.088 5.4 1.865 6.65 Example 4 1.87 1.41 8 1.997 6.85 Example 5 2.11 1.63 8 1.95 6.62 Example 6 3.06 2.426 15 2.13 5.89 Comparative Example 1 0.71 0.48 3 2.21 5.68 Comparative Example 2 1.88 1.68 12 2.08 5.87 Comparative Example 3 10.032 8.487 36 1.628 5.08 Comparative Example 4 4.428 3.286 21 2.231 5.47 Comparative Example 5 3.577 2.681 18 2.254 5.48

[0102] Figures 1 to 11 The SEM images of the silver powders obtained in Examples 1 to 6 and Comparative Examples 1 to 5 are shown in Table 1 and Figures 1 to 11 It can be seen that the silver powders of Examples 1 to 6 have good dispersibility, a low particle size distribution width (Span), good particle fluidity, and a large tap density. Although the silver powder in Example 6 is slightly agglomerated and the overall tap density of the silver powder is reduced, there is still enough small-particle silver powder to fill between the large-particle silver powder, and the tap density can still reach 5.89 g / cm 3 , and it is not easy to agglomerate in the subsequent conductive paste preparation process; Comparative Example 1 Figure 7 There is no large or small powder in the middle, all are small powder, and the tap density is low; Comparative Example 2 Figure 8 It is shown that there is too much large powder and almost no small powder. In the process of preparing the slurry, due to the lack of small powder filling, the large powder is easy to agglomerate, and its fluidity is poor, resulting in a decrease in its performance; in Comparative Example 3, the reducing property of the reducing agent used is very strong, resulting in a significant increase in the average particle size, D50, and D100 of the product silver powder, and a decrease in the overall tap density of the silver powder; in Comparative Examples 4 and 5, only organic amine solution or alcohol amine solution is used for reduction before and after, although large and small powders are also produced in the product silver powder, the particle size of both small and large powders is significantly enlarged, the particles are obviously agglomerated, the powder dispersibility is poor, and the tap density is also low.

[0103] The silver particles of the present invention can be applied to conductive silver paste. First, the tap density has an important influence on the thick film microstructure of the conductive silver paste. The silver powder particles with high tap density in Examples 1 to 6 are more likely to form a uniformly dispersed state in the slurry, which can reduce the aggregation between the silver powder particles, thereby obtaining a better microstructure. When preparing a thick film, the uniform dispersion of the silver powder particles can make the film layer denser, reduce the porosity, and improve the conductivity. The silver powder particles with low tap density in Comparative Examples 1 to 5 are easy to gather together to form an uneven microstructure, resulting in an increase in the porosity of the film layer, thereby reducing the conductivity. Secondly, the tap density will also affect the electrical properties of the conductive silver paste. The silver powder particles with high tap density in Examples 1 to 6 have better conductivity, because the high tap density means that the contact area between the silver powder particles is larger and the electron conduction path is shorter. In addition, the silver powder particles with high tap density are also more likely to form a connected network in the film layer, which can provide more conductive paths and further improve the conductivity. The tap density of the silver powder will also affect the rheological properties of the conductive silver paste. Rheological properties refer to the physical properties of the conductive silver paste during processing, such as viscosity, fluidity, etc. The silver powder particles with high tap density in Examples 1 to 6 are easier to disperse evenly in the slurry, which can reduce the viscosity of the slurry, improve fluidity, and facilitate processing and molding. On the contrary, the silver powder particles with low tap density in Comparative Examples 1 to 5 are easy to aggregate together, forming a higher viscosity, reducing the fluidity of the slurry and increasing the difficulty of processing.

[0104] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing silver particles, characterized in that: The following steps are involved: The silver salt is dispersed in an alcohol amine solution and then reacted with an organic amine solution to obtain the silver particles.

2. The method for preparing silver particles according to claim 1, characterized in that: The preparation method meets at least one of the following conditions: (I) the molar ratio of the alcoholamine compound in the alcoholamine solution to the silver ions in the silver salt is 0.05 to 5:1; (II) the molar ratio of the organic amine compound in the organic amine solution to the silver ion in the silver salt is 0.005 to 0.15:1; (III) controlling the pH of the organic amine solution to be 10-13.

3. The method for preparing silver particles according to claim 1, characterized in that: The alcoholamine solution includes a solution of at least one of diethanolamine, methyldiethanolamine, ethanolamine, dimethylethanolamine, diglycolamine, isopropanolamine, triisopropanolamine, oleic acid diethanolamide, stearic acid diethanolamide, lauric acid diethanolamide and octadecyl diethanolamine.

4. The method for preparing silver particles according to claim 1, characterized in that: The organic amine solution includes a solution of at least one of triethylamine, N-ethyldiisopropylamine, tri-n-propylamine, triisopropylamine, tri-n-butylamine, cyclohexylamine, dimethyloctylamine, dimethyldecylamine, tri(3,6-dioxaheptyl)amine and octylamine.

5. The method for preparing silver particles according to claim 1, characterized in that: The preparation method comprises the following steps: dispersing the silver salt in an alcohol amine solution, adding a dispersant, and then reacting with an organic amine solution.

6. The method for preparing silver particles according to claim 5, characterized in that: The dispersant includes at least one of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, sodium citrate, sodium lauryl sulfate, hexadecyltrimethylammonium bromide, gelatin, methylcellulose, citric acid, Tween 60, propionic acid, caprylic acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, acrylic acid, oleic acid, linoleic acid, arachidonic acid, and ricinoleic acid.

7. The method for preparing silver particles according to claim 1, characterized in that: The preparation method meets at least one of the following conditions: (I) the reaction is a hydrothermal reaction; (II) the reaction temperature of the reaction is 75 to 235°C; (III) The reaction time of the reaction is 0.5 to 12 hours; (IV) The reaction is carried out under stirring at a stirring rate of 200 to 500 rpm.

8. Silver particles obtained by the method for preparing silver particles according to any one of claims 1 to 7.

9. The silver particles according to claim 8, characterized in that: The silver particles satisfy at least one of the following conditions: (I) an average particle size of 1.0 to 3.1 μm; (II) D50 is less than 3.0 μm; (III) D100 is less than 20 μm; (IV) Span is less than 2.20; (V) Tap density is 5.80g / cm 3 above.

10. A conductive paste comprising silver particles prepared by the method for preparing silver particles according to any one of claims 1 to 7; or the silver particles according to claim 8 or 9.

Citation Information

Patent Citations

  • Method of producing fine-particle copper powders

    CN101237952A

  • Conductive material and process

    CN104024351A

  • Silver-zinc doped Raney copper catalyst as well as preparation method and application thereof

    CN111085221A

  • Nano-silver particle and preparation method thereof, nano-silver paste and welded joint

    CN113560562A

  • Silver nanoparticle and production method therefor

    JP2007063580A

Cited By

  • Silver particles and preparation method and application thereof

    CN119634744A

  • Silver particles, method for their production and use thereof

    CN119634744B

  • High tap density silver powder, preparation method therefor, and use thereof

    WO2026082219A1